Communication in the instructional design of a technical vocational and livelihood course at a senior high school in Los Banos, Laguna, Philippines - Velasco, Maria Dominique C. (The Philippine Journal of Development Communication, 2017)
Research about communication in instructional systems design has been overlooked in previous studies in the field of educational communication. To address the gap, this study analyzed the communication process that took place in each stage of the instructional design for a technical vocational and livelihood (TVL) track on bread and pastry production (BPP). Bread and pastry production is one of the specialized courses offered in the TVL track for K-12 students in the Philippines.